PIM1 Expression And Regulatory Mechanisms: Decoding Its Significance In Liver Hepatocellular Carcinoma (LIHC) Pathogenesis - Muhammad Asghar Khan , Abdullah Sethar , Sanobar Gull , Bushra Munir , Nimra Arshad , Imtiaz Ali Soomro , Zeshan Habib , Tehseen Zafar; Israr Khan , Hafeez Ullah , Rizwana Sultan , Jamal Muhammad Khan , Anam Aftab (Migration Letters, 2024)
The investigation focused on explaining the role of PIM1 expression and its regulatory mechanism in liver hepatocellular carcinoma (LIHC). Using the UALCAN database, PIM1 expression assessment revealed a critical down-regulation in malignant cells as compared with normal controls, suggesting its contribution in LIHC proliferation. Further, taking apart PIM1 expression across various boundaries showed unsurprising down-regulation in different cancer development stages, racial groups, genders and age classes inside LIHC patients, characteristics for its essential role in cancer proliferation. Validation of PIM1 expression done by Utilizing the GEPIA2.0 database, which showed PIM1 was lowly expressed in LIHC cancer as compared to normal control samples. Additionally, dismantling PIM1 validation across different stages of cancer showed dysregulation in all four stage with highest expression in stage III and the lowest expression in stage IV. Subsequently, this study investigated the promoter methylation level of PIM1, elucidating a critical correlation between LIHC samples and normal control samples. Analyzing promoter methylation across v[1]arious clinical parameters uncovered huge variations, with particular methylation patterns seen across cancer stages, race groups, genders and age groups. Survival analysis(OS and RFS) utilizing the KM plotter tool showed an epic association between PIM1 expression levels in LIHC patients, with low PIM1 expression exhibited with higher overall survival (OS) while high PIM1 expression experienced shorter DFS. Further upon validation of results of PIM1 expression level. We divided the LIHC patients into low and high expression groups of PIM1. In LIHC, high PIM1 expression level was associated with good overall survival (OS) while low PIM1 expression level was associated with good DFS in LIHC patients. Additionally, mutational analysis utilizing the cBioPortal stage revealed that no critical change found in LIHC samples. Overall, these findings cause to notice the intricate contribution of PIM1 in LIHC pathogenesis, underlining its importance as a prognostic biomarker and supportive therapeutic agent in LIHC management.